إشكالية انتهاء كفالة الطفل في قانون الأسرة والقضاء الجزائري: THE PROBLEM OF ENDING CHILD SPONSORSHIP IN ALGERIAN FAMILY AND JUDICIAL LAW - Mechouet, Halima; Soualhi, Asma Akli (Malaysian Journal of Syariah and Law, 2021)
Abstract in English: In the article 46, the Algerian Family Code stipulates the following: "Adoption is prohibited by both the Sharia and Law". Therefore, it is clearly understood that the interdiction of adoption doesn’t contradict the Islamic law (Sharia). But due - on one hand - to the confusion in Algerian society with regard to the conception of adoption with all its consequences, and on the other hand the difficult situation of many abandoned children and the suffering of many families who are not blessed with the fertility or the capacity of reproduction, the Algerian legislature has been forced to find solutions to such difficult cases. Therefore, a child support legislation (guardianship or sponsorship) has been established under the following Articles 116 and 125 of the Family Code. The study was based on the Algerian laws on the issue of the termination of child sponsorship and applied by the Algerian judiciary. The problem of the study is to know the cases of termination of child sponsorship in the Algerian family law, and the position of the Algerian judiciary on this issue. This study aims to mention the cases in which the sponsorship of the child ends in the Algerian family law, and to discuss some of the Algerian judicial decisions issued by the Supreme Court, related to the subject of the study in question. The study relied on the analytical method, in order to analyze legal texts and discuss judicial decisions. The study concluded that the Algerian family law stipulated some cases in which the sponsorship of the child ends, and neglected to mention other cases. Abstract in Arabic: لقد نص المشرع الجزائري في المادة 46 من قانون الأسرة على ما يلي: "يمنع التبني شرعا وقانونا".يتضح من تحليل هذه المادة أن المشرع منع الآخذ بنظام التبني تماشياً مع أحكام الشريعة الإسلامية. لكنه، ونظرا للمشاكل المترتبة على قضية التبني في المجتمع الجزائري من أخذ وردو كذلك بالنسبة للوضعية الصعبة لبعض الأطفال المهملين، وكذا معاناة بعض الأسر التي لا تنعم بالإنجاب، التجأ المشرع الجزائري إلى حل يتجلى في الكفالة، فنظم أحكامها في المواد من 116 إلى 125 من قانون الأسرة. استندت الدراسة إلى القوانين الجزائرية الخاصة بموضوع انتهاء كفالة الطفل والمطبقة من طرف القضاء الجزائري. تتمثل إشكالية الدراسة في معرفة حالات انتهاء كفالة الطفل في قانون الأسرة الجزائري، وموقف القضاء الجزائري من هذه المسألة. تهدف هذه الدراسة إلى ذكر الحالات التي تنتهي بها كفالة الطفل في قانون الأسرة الجزائري،ومناقشة بعض القرارات القضائية الجزائرية الصادرة عن المحكمة العليا،والمتعلقة بموضوع الدراسة محل البحث. لقد اعتمدت الدراسة على المنهج التحليلي، وذلك من أجل تحليل النصوص القانونية ومناقشة القرارات القضائية. لقد توصلت الدراسة إلى أن قانون الأسرة الجزائري نص على بعض الحالات التي تنتهي بها كفالة الطفل،وأغفل عن ذكر الحالات الأخرى